Rural food security in Mutare District, Zimbabwe, 1947-2010 - Kusena, Bernard (Rhodes University, Faculty of Humanities, Department of History, 2019)
By taking Mutare District as its lens to explore the dynamics of rural food security in Zimbabwe, this thesis assesses the role of the state in tackling hunger among its rural populations. It examines the impact of colonial and post-colonial food policy on efforts to combat food insecurity. The thesis explores the uneasy options pursued by rural communities in response to droughts and other threats of hunger. It identifies and ranks crop failure as the chief culprit to the district's efforts towards food security. The thesis illustrates the contestations between the state and its rural people over which sustainable approaches to adopt in order to end hunger and how such debates continually shaped policy. It grapples with questions about the various understandings of food security advanced by scholars within the rural African context. It demonstrates, for instance, that the post-colonial state inherited an erstwhile crop production structure which shunned food crops in favour of cash crops. There was obvious bias against local preferences for a robust, home-grown food regime which did not put rural livelihoods at risk of starvation. The thesis also argues that food can be used as an instrument of war as evidenced during the liberation struggle when the vast majority of people residing in rural areas, particularly women and children, were pushed to the edges of survival. In addition, the thesis demonstrates that the infamous Marange diamonds turned out to be a curse rather than a blessing due to the state's lack of transparency in the beneficiation chain. It concludes by a detailed examination of the political economy of food aid, demonstrating why donors have not succeeded for long to combat hunger in the district. In light of this background, the thesis provides a more nuanced analysis of the whole question of rural food security using archival material, newspapers, government and civil society reports, interviews and field observation. The thesis benefits from the use of a multi-pronged theoretical framework to capture the disparate themes that form the bedrock of this study.
Keywords: Mutare (Zimbabwe) -- History; Zimbabwe -- History; Food security -- Zimbabwe; Poverty -- Zimbabwe; Rural pooer -- Zimbabwe; Crop losses -- Zimbabwe; Food relief -- Zimbabwe